PENINGKATAN PENGETAHUAN IBU NIFAS TENTANG INISIASI MENYUSUI DINI DAN ASI EKSLUSIF MELALUI PROGRAM EDUKASI - Saleh Baso, Yusriani; Sukirno, Sukirno; I Putu Juni Andika; Austy, Vinory; Paramita Dewi, Adinda; Kartikasari, Mentari (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
Early Initiation of Breastfeeding (IMD) and exclusive breastfeeding are maternal and child health interventions that play a crucial role in reducing the risk of neonatal infection, improving infant immune resilience, and supporting optimal public health. However, the lack of knowledge and skills of postpartum mothers remains a major barrier to implementing these practices. This Community Service (PKM) activity aims to improve postpartum mothers' knowledge and skills regarding Early Initiation of Breastfeeding (IMD) and exclusive breastfeeding through a participatory learning-based educational program. The activity method includes a pretest, material delivery using interactive media, discussion and question-and-answer sessions, and demonstrations of correct breastfeeding positions and attachments. Evaluation was conducted through a posttest on knowledge and observation of breastfeeding practices. The activity results showed a significant increase in postpartum mothers' knowledge and improved ability to practice Early Initiation of Breastfeeding (IMD) and effective breastfeeding techniques. This increased knowledge and skills are supporting factors in the success of exclusive breastfeeding until six months of age and have the potential to reduce the risk of neonatal infection through colostrum provision and appropriate breastfeeding practices. This educational program contributes as a promotional and preventive effort to improve maternal and infant health and supports the strengthening of community-based health services.